Analisis Key Performance Indicator (KPI) dengan metode Balanced Scorecard dalam menghadapi Pasar Persaingan Energi Listrik di PT Indonesia Power - , Andy Adam ([Yogyakarta] : Universitas Gadjah Mada, 2013)
No doubt that the objective of the Balanced scorecard was to create a system which could measure the performance of an organization, and both to monitor and improve any deviation that occur. One of the biggest power plant company implemented the BSC framework as one of strategic management tools to communicate its strategic. BSC framework used to produce a strategic planning company that is more comprehensive not only limited to the financial perspective, but also extends to the three others, such as Customer, Process and Learning & Growth. Thus, strategic planning will produce a more comprehensive BSC.